Telepsychiatry in the Arab World: A Viewpoint Before and During COVID-19 - El Hayek, Samer (Neuropsychiatr Dis Treat, 2020)
PURPOSE: Telepsychiatry, a subset of telemedicine, has been increasingly studied to meet the growing demands for psychiatric care. The utility of telepsychiatry is relevant now more than ever as the world endures the COVID-19 global pandemic. This paper describes the prior state and the changes that the COVID-19 outbreak brought to telepsychiatry in a selected group of Arab countries of the Middle East and North Africa (MENA) region. PATIENTS AND METHODS: We invited twelve early-career psychiatrists from different Arab nations to share information related to telepsychiatry in their respective countries before and during the COVID-19 pandemic. The information was collected using a semi-structured guide. This was complemented by a search for relevant articles in five search engines using terms such as “COVID-19,” “telepsychiatry,” and “Arab world”. RESULTS: Before the pandemic, digital mental health services were provided in several Arab countries, mainly through hotlines and messaging services. The COVID-19 pandemic has marked a major shift in digital psychiatric services in the Arab MENA world, through the transformation of many clinics and some hospitals into digital mental health systems. Many non-governmental organizations also started remote initiatives for psychological support and psychiatric counseling. Three main barriers of patient-related, healthcare-related, and system-related hurdles of using telepsychiatry emanated from the analysis. CONCLUSION: The use of digital mental health services varies between different Arab countries. Even though some nations have laws that regulate the provision of such services, most struggle with multifactorial barriers. As affordable and attainable solutions cannot only rely on training and recruiting more psychiatrists, telepsychiatry would help meet the exceeding demands in the Arab world, particularly after the COVID-19 outbreak.